ANALISA DAN PERANCANGAN START-UP PEMESANAN JASA DESAIN GRAFIS BERBASIS APLIKASI MOBILE - Aditya RIo Setiawan; Septiawan Dwianto; Adhitya Dhani Pradana (LPPM Universitas Putera Batam, 2023)
Graphic design is a visual form that uses images to convey information or messages as quickly as possible. There are still many people who find it difficult to find design services that fit their needs and budget. Some problems found in finding suitable design services include difficulty finding affordable services, lack of adequate quality of service, and lack of transparency in the booking process. The application